Does Elevated Morning Prolactin Concentration in Children Always Mean the Diagnosis of Hyperprolactinemia? - Stawerska, R.; Smyczyńska, J.; Hilczer, M.; Lewiński, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Aim: It has recently been suggested that prolactin (Prl) level above the upper limit of normal range, recorded in a single measurement in serum is enough to diagnose hyperprolactinemia (HPrl). The aim of the study was the analysis of the circadian rhythm of Prl secretion in children with an increased morning Prl concentration in order to establish whether it is a real hyperprolactinemic state or not.Material and methods: The analysis comprised a group of 44 children (32 boys and 12 girls, aged from 4.2 to 14.1 years, mean±SD: 10.4±3.5 years) with either short stature or precocious puberty, with an elevated Prl concentration at 8:00 a.m., suggesting hyperprolactinemic state. In all patients the circadian Prl secretion profile was assessed on the basis of Prl concentrations in 9 blood samples, collected in 3-h intervals. An analysis of the circadian Prl rhythm was performed. Depending on the medical history and the magnetic resonance imaging result, the children were divided into the following groups: A – congenital disorders of hypothalamic-pituitary region (n=10); B – acquired disorders of hypothalamic-pituitary region (other than pituitary adenomas) (n=15), C – pituitary adenomas (n=19). The control group consisted of 14 healthy children (9 boys and 5 girls), aged from 5.2 to 14.3 years, mean±SD: 10.8±3.2 years.Results: In only 18 children (41%), apart from a higher morning Prl concentration, an elevated Prl concentration at other time points was observed and the circadian rhythm was disturbed, implying hyperprolactinemic state (2 children from Group A, 8 from Group B and 8 form Group C). In the remaining 26 children (59%), higher morning Prl concentrations were not accompanied by elevated Prl concentrations at other time points of the circadian profile.Conclusions: In children with elevated Prl concentrations in the morning, a circadian Prl secretion profile should be performed in order to avoid overdiagnosing of continuous HPrl. In children with the presence of pituitary adenoma and increased morning Prl concentrations, the diagnosis of Prl-secreting adenoma is not completely obvious.
Keywords: prolactin circadian rhythm; pituitary hypoplasia; pituitary stalk interruption syndrome; microadenoma of hypophysis; growth hormone deficiency; precocious puberty